Gambaran Stres Akademik Mahasiswa Selama Pembelajaran Daring Pada Masa Pandemi Covid-19 - Risma, Rini Utari; Nurhasanah, Nurhasanah; Nasution, Jamilah Aini (Jurnal Suloh, 2022)
The purpose of the study is to explain the picture of student academic stress during online learning during the COVID-19 pandemic. The research method used is descriptive quantitative. The population in this study was an active student at the undergraduate level of Syiah Kuala University, and samples were taken based on simple random sampling techniques of 393 people from the class of 2017 to 2021. The data collection technique used is an academic stress scale adapted and modified from Gadzella's Student Life Stress Inventory (SLSI) measuring instrument consisting of 48 statement items. Data collection is done using the Google form platform. The data analysis technique used is descriptive analysis. The results showed that the level of academic stress during online learning during the COVID-19 pandemic experienced by respondents in this study was in the medium category of 285 people with a percentage of 72.5%, in the high category as many as 79 people with a percentage of 20.1%, and in the low category as many as 29 people with a percentage of 7.4%.